The effects of the ginger supplements on inflammatory parameters in type 2 diabetes patients: a systematic review and meta-analysis of randomised controlled trials - Mohammad, Abolfathi; Falahi, Ebrahim; Mohd Yusof, Barakatun Nisak; Nor Hanipah, Zubaidah; Sabran, Mohd Redzwan; Mohamad Yusof, Loqman; Gheitasvand, Mohsen (Elsevier BV, 2021)
Objectives: The effect of ginger supplements on inflammatory biomarkers and oxidative stress in patients with type 2 diabetes (T2DM) has been investigated, but findings are inconsistent. This systematic review and meta-analysis were conducted to determine the effects of ginger supplementation on inflammatory parameters (high-sensitivity C-reactive protein [hs-CRP], tumour necrosis factor-alpha [TNF-a], and interleukin-6 [IL-6]) in patients with T2DM. Methods: We performed a systematic search using PubMed, Scopus, Cochrane Library, Web of Science for randomised controlled trials (RCTs), published until March 17, 2021. The quality assessment was carried out using the Cochrane Collaboration risk of bias tool. The Q-test and I 2 tests were used for the determination of heterogeneity of the included studies. Data were pooled using a random-effects model, and weighted mean difference (WMD) was used for the overall effect size. Results: Pooled findings of the five RCTs demonstrated that ginger supplementations had significantly reduced hs-CRP (WMD 0.42 mg/L; 95% CI, 0.78, 0.05, P ¼ 0.03), TNF-a (2.13 pg/mL; 95% CI: 3.41, 0.86, P ¼ 0.001), and IL-6 (WMD: 0.61 pg/mL; 95% CI: 0.92, 0.30, P ¼ 0.001) levels in patients with T2DM. The quality assessment of the studies showed that all of the included studies were at high risk of bias. Conclusions: The meta-analysis shows that ginger supplementations reduced inflammatory parameters in patients with T2DM. Nonetheless, the reduction is relatively small, and its meaningful clinical effects are unknown. Future high-quality RCTs are needed to confirm the beneficial effects of ginger supplementation in patients with T2DM.